Perancangan Identitas Visual PT. Voyager Academy International sebagai Upaya Membangun Citra Lembaga Pelatihan Kerja - Muhammad Zidhan Gumilang; Dwi Candra Purnamasari (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
PT. Voyager Academy International is a Job Training Institution (Lembaga Pelatihan Kerja/LPK) specializing in the international cruise ship and hospitality industries. As a newly established institution, the company has not yet developed a visual identity capable of representing its character in a professional and consistent manner. Therefore, designing a visual identity is considered essential to strengthen the company's corporate image. This study aims to design the visual identity of PT. Voyager Academy International through the development of a logo, color palette, and typography that reflect the company's characteristics. The research employed a descriptive qualitative method using observation, interviews, documentation, and literature review as data collection techniques. The collected data were analyzed using the 5W+1H method, while the design process followed Robin Landa's 5 Phases of Graphic Design Process, consisting of Orientation, Analysis and Strategy, Conceptual Design, Design Development, and Implementation. The result of this study is a new visual identity in the form of a monogram logo that combines cruise ship elements, ocean waves, and the initials VAI to symbolize the journey toward a global career. The visual identity is supported by a color palette, typography, grid system, logo usage guidelines, and its implementation across various corporate media, including uniforms, ID cards, lanyards, and stationery. The proposed visual identity is expected to strengthen the corporate image of PT. Voyager Academy International as a professional, recognizable, and trustworthy job training institution.